VO2max development in children and adolescents and its importance in judo - Sklebar, T.; Plecko, M.; Bohacek, I. (The Arts and Sciences of Judo, 2023)
Maximum oxygen uptake serves as the gold standard for assessing aerobic fitness, repmsenting the highest attainable rate of whole-body oxygen uptake during exercise involving large muscle groups. In judo, a physically demanding and high-intensity intermittent sport, advanced technical skills and strategic proficiency are essential for success as athletes engage in multiple actions within time-limited matches. This review aimed to analyse studies comparing VO2max development and trainability of trained and untrained children and adolescents in different stages of training, to determine the significance of aerobic training in judo and explore alternative training approaches for young judoka. is measured using a cardiopulrnonary exercise test (CPET). Training-induced increases in VO2max have been observed to be influenced by factors such as increased stroke volume and greater arteriovenous oxygen content difference. The baseline values and trainability of VO2max appear to be partially infiuenced by genetics. The development of VO2max in children and adolescents follows a growth and maturation process, with age and sex-related differences observed. Trained individuals generally exhibit higher VO2max values, compared to their untrained counterparts, with absolute VO2max increasing linearly until around the age of 15 for both boys and girls. In competitive judo, aerobic fitness may not be as crucial as anaerobic fitness, as elite judoka have Iower VO2max values compared to athletes in other endurance sports. While it still beneficial to train aerobic fitness, the main focus for young judoka should pemaps be on developing anaembic capacity, power, dynamic strength, and maintaining Iower body fat percentages.